Babesia microti alleviates disease manifestations caused by Plasmodium berghei ANKA in murine co-infection model of complicated malaria - Zafar, Iqra; Taniguchi, Tomoyo; Baghdadi, Hanadi B.; Kondoh, Daisuke; Rizk, Mohamed Abdo; Galon, Eloiza May; Ji, Shengwei; El-Sayed, Shimaa Abd El-Salam; Do, Thom; Li, Hang; Amer, Moaz M.; Zhuowei, Ma; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
Malaria remains one of the significant health issues accounting for 2.6% of the total global disease burden, and the efforts to eliminate this menace continue. The key focus is to develop an efficient and long-term immunity to this disease via vaccination or therapeutic approach, and innovative strategies would enable us to achieve this target. Previously, by the use of mouse co-infection disease model, cross-protection was illustrated between Babesia microti and Plasmodium chabaudi. Hence, this study was planned to elucidate the impact of acute B. microti Peabody mjr and Plasmodium berghei ANKA co-infection on the consequence of complicated malaria in the This is a provisional file, not the final typeset article C57BL/6J mouse model of malaria. Furthermore, immune response and pathological features were analyzed, and the course of the disease was compared among experimental groups. Our study established that acute B. microti infection activated the immunity which was otherwise, suppressed by P. berghei. The immunosuppressive tissue microenvironment was counteracted as evidenced by the enhanced immune cell population in co-infected mice, in contrast to P. berghei-infected control mice. Parasite sequestration in the brain, liver, lung, and spleen of co-infected mice was significantly decreased and tissue injury was ameliorated. Meanwhile, the serum levels of IFN-γ, TNF-α, and IL-12p70 were reduced while the secretion of IL-10 was promoted in co-infected mice. Eventually, co-infected mice showed an extended rate of survival. Hereby, the principal cytokines associated with the severity of malaria by P. berghei infection were TNF-α, IFN-γ, and IL-12p70. Moreover, it was evident from our flow cytometry results that innate immunity is crucial and macrophages are at the frontline of immunity against P. berghei infection. Our study recommended further investigations to shed light on the effects of babesiosis in suppressing malaria with the goal of developing Babesia-based therapy against malaria.